War crimes and just war - May, Larry (Cambridge University Press, 2007)
War crimes are international crimes committed during armed conflict. Larry May argues that the best way to understand war crimes is as crimes against humanness rather than as violations of justice. Throughout, May demonstrates that the principle of humanness in the cornerstone of international humanitarian law, and is itself the basis of the traditional principles of discrimination, necessity, and proportionality.